Activity Evaluation of some Plant Extracted Oils in Controling of Algal Growth - AL-Husseinawi, Noor; Jawad, Abdul-Latif; AL-Shamma, Laith (Iraqi Journal of Science, 2023)
This study includes isolation, purification, and identification of algae from the canal around Baghdad university Al-jadriah. Four unialgal cultures were obtained. These algal cultures included 3 species of cyanophyta ( Nostoc carneum, Westillopesis prolifica, Chroococcus turgidus), 1 species of chlorophyta (Chlorella vulgaris) . Different plants belonging to different families were collected and extracted for their oils which were Ricinus communis and Sesamum indicum (seeds), Matricaria chamomilla (flowers) .However, antialgal activity of the extracted oils were evaluated the isolated algae with 7 concentrations (0.09, 0.3, 0.5, 1, 10, 20 , 30) % using the agar wells diffusion method. Results showed that R. communis oil was more effective against isolated algae followed by Sesamum indicum oil .The volatile oil extracted from M. chamomilla was less effective. C. turgidus was the most sensitive to attack by oils followed by N. carneum .While W. prolifica was the less sensitive alga, followed by Chlorella vulgaris . Chemical composition of the most effective oil (R. communis ) was analyzed by HPLC which showed that 5 terpens compounds found in this oil (Alpha-pinene, Thujone, Camphor,1-8Cineole, Camphene).